Search for the doubly charmed baryon Ξ+cc - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dembiski, H.-P.; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; et al. (Science China. Physics, mechanics & astronomy, 2020)
A search for the doubly charmed baryon $$Ξ_{cc}^+$$ is performed through its decay to the $$Λ_c^ + {K^ -}{π ^ +}$$ final state, using proton-proton collision data collected with the LHCb detector at centre-of-mass energies of 7, 8 and 13 TeV. The data correspond to a total integrated luminosity of 9 fb−1. No significant signal is observed in the mass range from 3.4 to 3.8 GeV/c2. Upper limits are set at 95% credibility level on the ratio of the $$Ξ_{cc}^+$$ production cross-section times the branching fraction to that of $$Λ_c^ + $$ and $$Ξ_{cc}^{+ +}$$ baryons. The limits are determined as functions of the $$Ξ_{cc}^+$$ mass for different lifetime hypotheses, in the rapidity range from 2.0 to 4.5 and the transverse momentum range from 4 to 15 GeV/c.
Im Titel ist "+" hochgestellt und "cc" tiefgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, H.-P. Dembinski, M. Dziewiecki, D. Gerick, J. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, H. Malygina, J. Marks, N. Meinert, S. Neubert, A. Piucci, M. Schmelling, N. Skidmore, S. Stemmle, U. Uwer, H. Viemann, R. Waldi, M. Zavertyaev, A. Zhelezov und weitere 879
Gesehen am 14.04.2021